2016
DOI: 10.3389/fpsyg.2016.00196
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Knowledge Representation and the Parameterization of Context

Abstract: Though instrumental in numerous disciplines, context has no universally accepted definition. In specialized knowledge resources it is timely and necessary to parameterize context with a view to more effectively facilitating knowledge representation, understanding, and acquisition, the main aims of terminological knowledge bases. This entails distinguishing different types of context as well as how they interact with each other. This is not a simple objective to achieve despite the fact that specialized discour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 93 publications
0
13
0
2
Order By: Relevance
“…However, with the growth of digital mental health interventions changing the ways in which mental health care is delivered, peer support is increasingly being offered via digital technologies known as digital peer support. Digital peer support is defined as automated or live peer support services that can be delivered through multiple modalities [ 16 ], such as web-based peer support [ 17 ], smartphone-supported interventions [ 18 , 19 ], and web-based peer-to-peer networks [ 20 ]. A recent systematic review concluded that digital peer support appears to be both acceptable and feasible, with a strong potential for clinical effectiveness [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the growth of digital mental health interventions changing the ways in which mental health care is delivered, peer support is increasingly being offered via digital technologies known as digital peer support. Digital peer support is defined as automated or live peer support services that can be delivered through multiple modalities [ 16 ], such as web-based peer support [ 17 ], smartphone-supported interventions [ 18 , 19 ], and web-based peer-to-peer networks [ 20 ]. A recent systematic review concluded that digital peer support appears to be both acceptable and feasible, with a strong potential for clinical effectiveness [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The central aim of this thesis is to investigate the causal relationship between context, cognition, and language structure using a cultural evolutionary framework. What constitutes a context, and how it interacts with the structure and use of language, is still subject to considerable debate Faber & León-Araúz, 2016). As Herb Clark noted in motivating the use of his term common ground:…”
Section: Introductionmentioning
confidence: 99%
“…In Terminology, the usefulness of embedding concepts in situations has also been highlighted as a way of enriching conceptual representations (Dubuc and Lauriston 1997;Faber 2012;Temmerman 2013). Although context is often regarded as the segment/s which precede or follow a word or phrase (Lyons 1995), it can also be a related situation, events, or information that help users to understand something, and which reflect a specific knowledge profile (Kecskes 2014;Faber and León-Araúz 2016). The specification of contexts should thus take place at multiple levels that range from concept to frame.…”
Section: Theoretical Backgroundmentioning
confidence: 99%